Synthesis and Characterization of Gallic Acid Conjugated Glycol Chitosans for Tissue Adhesive Applications - Park, Seul Gi; Li, Mei-Xian; Eom, Ji Hwan; Suh, Eun Yeong; Cho, Woo Kyung; Joung, Yoon Ki; Huh, Kang Moo (POLYMER SOC KOREA, 2021)
In this study, we developed self-crosslinkable and self-healing hydrogels by conjugating biocompatible and biodegradable glycol chitosan (GC) with biofunctional gallic acid (GA) and evaluated their potential application as a new tissue adhesive biomaterial. A series of GA-GC derivatives with different GA content were synthesized by varying the feed molar ratio of GA and their hydrogels were prepared via self-crosslinking reaction between pyrogallol groups of GA. The self-healing ability of GA-GC hydrogels was confirmed by rheological analysis, and their mechanical strength and tissue adhesion strength were observed to increase as the GA content of the hydrogels increased. The GA-GC hydrogels with biodegradability and low cytotoxicity would be useful as new tissue adhesive biomaterials.
Keywords: FIBRIN; ANTIOXIDANT; PYROGALLOL; HYDROGELS; SEALANTS; CHITIN